PENGARUH INDEPENDENSI, OBJEKTIVITAS, PENGETAHUAN, PENGALAMAN KERJA, INTEGRITAS TERHADAP KUALITAS AUDIT (STUDI PADA INSPEKTORAT PROVINSI JAWA BARAT TAHUN 2018) - Yohana Ariska Sihombing; Dedik Nur Triyanto (UNIB Press, 2019)
Audit quality is audit conducted in accordance with the standard so that it is able to recognized and report in case of violations committed clients. The purpose of this study is to analyse the things that relate to the quality of the audit. This research intends to influence independent variable information simultaneously and is partial. In this research, which became the independent variables namely independence, objectivity, knowledge, work experience, and integrity while the dependent varaibel i.e. the quality of audits.The population in this research is the auditor of internal Inspectorate West Java province year 2018 by the number of respondents as many as 31 people and sampling techniques in the study of saturated samples is random sampling. Methods of analysis in this research is descriptive statistics analysis and multiple regression analysis using SPSS software 23.Based on the test results, the value of R square on this research is of 54.8%, it means that independent varibel influenced dependent variabel 54,8%. While the rest amounted to 45.2% influenced by other factors. Simultaneously varaibel the independence, objectivity, knowledge, work experience, and the integrity of the influential significantly to the quality of the audit. Partially variable positive effect significantly to certify the quality of audits. Partially variable objectivity, knowledge, work experience, and do not affect the integrity of the quality audit. Key Words : Independence, Objectivity, Knowledge, Work Experience, Integrity, Audit Quality